2004
DOI: 10.1103/physrevlett.92.046102
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding in MixedOH+H2OOverlayers on Pt(111)

Abstract: The stability of OH on Pt(111) has been investigated to determine the role of hydrogen bonding in stabilizing the overlayer. We find that the optimal structure is a mixed (OH+H2O) phase, confirming recent density-functional theory predictions. The reaction O+3H(2)O forms a hexagonal (sqrt[3]xsqrt[3])R30 degrees -(OH+H2O) lattice with a weak (3x3) superstructure, caused by ordering of the hydrogen bonds. The mixed overlayer can accommodate a range of H(2)O/OH compositions but becomes less stable as the H2O cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
104
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(120 citation statements)
references
References 22 publications
14
104
1
1
Order By: Relevance
“…This is in accordance with previous findings summarized in the so-called 2D water rules 32,33 and also with results for the extended H-bonded mixed H 2 O / OH phases on Pt͑111͒. [6][7][8][9][10][11][12] The oxygen atoms in the H 2 O and OH molecules are nearly coplanar, with a small corrugation of approximately 0.2 Å, which can reach a value of 0.5 Å at the edges. In a separate study of the water structures formed on Pd and Ru at temperatures below 140 K, we observed that individual water molecules are often attached to the edges of single hexamers or clusters containing several hexagons.…”
Section: ͑I͒supporting
confidence: 78%
See 2 more Smart Citations
“…This is in accordance with previous findings summarized in the so-called 2D water rules 32,33 and also with results for the extended H-bonded mixed H 2 O / OH phases on Pt͑111͒. [6][7][8][9][10][11][12] The oxygen atoms in the H 2 O and OH molecules are nearly coplanar, with a small corrugation of approximately 0.2 Å, which can reach a value of 0.5 Å at the edges. In a separate study of the water structures formed on Pd and Ru at temperatures below 140 K, we observed that individual water molecules are often attached to the edges of single hexamers or clusters containing several hexagons.…”
Section: ͑I͒supporting
confidence: 78%
“…It also shows that the layer has a domain structure with narrow dimensions in one direction. [3][4][5] This is in contrast to the extended twodimensional ͑2D͒ hydrogen ͑H͒-bonding network formed on Pt͑111͒ [6][7][8][9][10][11][12] and with similar models on Ru͑0001͒ put forward based on theoretical modeling. 1,2 The detailed structure of the stable H 2 O -OH phase on Ru͑0001͒ remains unclear to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect has been observed in mixed OH/H 2 O monolayers on Pt(111) (OH in this case referring to a distinct molecule coadsorbed with water), where very stable, ordered hexagonal structures form at a 1:1 (OH:H 2 O) ratio as a result of alternating H-bond donor (H 2 O) and acceptor (OH) molecules 47,48 . Such a tendency towards donor/acceptor ordering is expected to occur as a general feature of water adsorption on hydroxylated oxide surfaces, to the extent this is compatible with the geometric features of the specific surface.…”
Section: Resultsmentioning
confidence: 61%
“…In the H 2 O*/HO* superstructure, half of the water molecules lie in a plane approximately parallel to the surface, and the other water molecules lie in a plane perpendicular to the surface with one hydrogen atom pointing away from the surface. 61,[206][207][208][209][210] …”
Section: Electrochemical Measurementsmentioning
confidence: 99%